The activity of the protease of human immunodeficiency virus type 1 is initiated at the membrane of infected cells before the release of viral proteins and is required for release to occur with maximum efficiency. - Kaplan, A H (1994)
The final steps in the production of the type C retroviruses include assembly of the viral core particle and release of virions from the surface of the infected cell. The core proteins are translated as part of one of two precursors, Gag and Gag/Pol, which are cleaved by a virally encoded protease. We examined the interaction between the processing of the human immunodeficiency virus type 1 Gag precursor and the membrane-based assembly and budding of virions. Our results indicate that cleavage by the viral protease is initiated at the membrane of the infected cell during virus release and that protease activity is required for virion release to occur with maximum efficiency.